Failed Experiences of the UN Role in Building Global Peace (Iraq, Syria) - Mahmood, Rebwar Kareem; Salih, Ibrahim Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The United Nations has played a positive role in its attempts to deal with some crises. However, it failed many times. In the modern era, the United Nations has failed to deal with the Iraq crises (2003-2017) and Syria crises (2011-2017), as part of its efforts to achieve its primary goal, which is to maintain international peace and security. The failure to achieve international peace is due to several reasons, both internal and external. Since the beginning of the crisis in Iraq and Syria, the United Nations has taken several political, economic and military steps to end the two crises separately. These unremitting attempts have witnessed convergence in the views of the many components and the different political forces that exist, with the purpose of arriving at an independent decision for both countries and then removing the danger from international peace and security. However, due to the large number of internal differences and the continuation of external interventions, the United Nations failed to deal with the crisis in both Iraq and Syria, which means failure to build world peace in the framework related to these two countries.